A numerical study on elliptical particle deposition with an immersed boundary-lattice Boltzmann method. (15th October 2022) - Wang, Wen-Quan; Wang, Jinling; Cui, Guanzhe; Pei, Junxian; Yan, Yan
Highlights: Angular velocity of particle has same direction whatever flow conditions or Reynolds number. Average deposition velocity and the aspect ratio present a closing parabola curve. Initial angle only changes the phase angle of the dynamic characteristic curve. Density ratio has a distinct and positive relationship with the settling velocity. Abstract: This paper presents a numerical study on elliptic particle deposition in a Newtonian fluid at low Reynolds numbers. The effects of inflow condition, Reynolds number, aspect ratio, initial angle, and density ratio on the dynamic characteristics of the particle are investigated. The results show that the absolute deposition velocity of the particle increases with the decrease of Reynolds number for all flow conditions. Although there is a slight difference between the uniform and the Poiseuille flows, the absolute deposition and angular velocities of the particle are enhanced by the shear flow. Moreover, the deposition, horizontal and angular velocities exhibit a periodic fluctuation with the dependent frequency of the inflow conditions and the Reynolds numbers. The relationship between the time-averaged deposition velocity and the aspect ratio presents a closing quadratic curve. The initial angle of the particle only affects the phase difference of motion but not changes the dynamic characteristics of the particle. Furthermore, the time-averaged deposition velocity of the particle is proportional to the density ratio.